A genetic signature including apolipoprotein Eε4 potentiates the risk of herpes simplex–associated Alzheimer's disease. Issue 1 (1st January 2019) - Lopatko Lindman, Karin; Weidung, Bodil; Olsson, Jan; Josefsson, Maria; Kok, Eloise; Johansson, Anders; Eriksson, Sture; Hallmans, Göran; Elgh, Fredrik; Lövheim, Hugo
Abstract: Introduction: Herpes simplex virus type 1 (HSV1) in combination with genetic susceptibility has previously been implicated in Alzheimer's disease (AD) pathogenesis. Methods: Plasma from 360 AD cases, obtained on average 9.6 years before diagnosis, and their age‐ and sex‐matched controls, were analyzed for anti–HSV1 immunoglobulin (Ig) G with enzyme‐linked immunosorbent assays (ELISAs). A POE genotype and nine other selected risk genes for AD were extracted from a genome‐wide association study analysis by deCODE genetics, Reykjavik, Iceland. Results: The interaction between APOEε 4 heterozygosity ( APOEε 2 /ε 4 or ε 3/ ε 4) and anti–HSV1 IgG carriage increased the risk of AD (OR 4.55, P  = .02). A genetic risk score based on the nine AD risk genes also interacted with anti–HSV1 IgG for the risk of developing AD (OR 2.35, P  = .01). Discussion: The present findings suggest that the APOEε 4 allele and other AD genetic risk factors might potentiate the risk of HSV1‐associated AD.